Genetic Mouse Models with Intestinal-Specific Tight Junction Deletion Resemble an Ulcerative Colitis Phenotype. (27th May 2017) - Stremmel, Wolfgang; Staffer, Simone; Schneider, Mathias Jochen; Gan-Schreier, Hongying; Wannhoff, Andreas; Stuhrmann, Nicole; Gauss, Annika; Wolburg, Hartwig; Mahringer, Anne; Swidsinski, Alexander; Efferth, Thomas
Abstract: Background and Aims: A key pathogenetic feature of ulcerative colitis [UC] is an intrinsic low mucus phosphatidylcholine[PC] content. Recently, a paracellular transport for PC across tight junctions[TJs] was described, suggesting TJ disturbance as a cause of diminished luminal PC transport. Therefore, we aimed to generate mutant mice with TJ deletion to evaluate whether a UC phenotype developed. Methods: CL57BL/6 control wild-type mice were compared to mutant mice with tamoxifen-induced villin-Cre-dependent intestinal deletion of kindlin 1 and 2. Results: Electron microscopy of mucosal biopsies obtained from both mutants before overt inflammation following only 2 days of tamoxifen exposure revealed a defective TJ morphology with extended paracellular space and, by light microscopy, expanded mucosal crypt lumina. PC secretion into mucus was reduced by >65% and the mucus PC content dropped by >50%, causing a >50 % decrease of mucus hydrophobicity in both mutants. Consequently, the microbiota was able to penetrate the submucosa. After 3 days of tamoxifen exposure, intestinal inflammation was present in both mutants, with loose bloody stools as well as macroscopic and histological features of colitis. Oral PC supplementation was able to suppress inflammation. By analogy, colonic biopsies obtained from patients with UC in remission also showed a defective epithelium with widened intercellular clefts, and enlarged crypt luminal diameters with functionally impaired luminal PC secretion. Conclusions: Genetic mouse models with intestinal deletion of kindlin 1 and 2 resulted in TJ deletion and revealed pathophysiological features of impaired PC secretion to the mucus leading to mucosal inflammation compatible with human UC.